O Estresse Psicossocial do Enfermeiro em Oncologia: uma Análise a partir da Escala Desequilíbrio Esforço-Recompensa - Machado Piereck de Sá, Graciela; Nascimento Pereira de Farias, Sheila; Fernandes Portela, Luciana; Harter Griep, Rosane; Rotenberg, Lúcia (Revista Brasileira de Cancerologia, 2014)
Introduction: This study examines the psychosocial stress in oncology nurses according to the effort-reward imbalance (ERI) model. This model is based on the relationship between efforts and rewards generated in the workplace and it is being used in occupational epidemiology research worldwide. Objective: To identify the factors associated with psychosocial stress among nurses. Method: We used the database of a cross-sectional study entitled “Nurses Health Study”, conducted in the 18 largest hospitals in the municipality of Rio de Janeiro between 2010 and 2011. This study was approved by the research ethics committees of the Oswaldo Cruz Foundation, the National Institute of Cancer and the School of Nursing Anna Nery. The present investigation included 211 (94%) nurses from the National Institute of Cancer. Data collection was based on a comprehensive self-administered questionnaire that included the ERI scale and questions on socio-demographic data, occupational variables and questions about health and health habits. Statistical analyses were based on the multivariate logistic regression. Adjusted odds ratios and respective 95% confidence interval were presented. Results: Younger nurses are approximately three times more likely to have a high ERI in comparison to older nurses (OR: 3,17; IC95%1,59-6,31); those who had the intention to leave their jobs have 13.26 more chance to have a high ERI (OR: 13,26; IC95%4,27-41,16). Conclusion: Younger nurses and those nurses who reported intention to leave their jobs have greater imbalance between effort expended and reward received at work. The issue of psychosocial stress at work deserves more attention, especially among oncology nurses.